2017
DOI: 10.1249/mss.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Heritable Determinants of Decompression Sickness in Rats

Abstract: This study offers evidence suggesting the inheritance of DCS resistance. Future research will focus on genetic and physiological comparisons between the initial strain and the new resistant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Also, as our results are in line with different study populations, collection methods and sample techniques, this tends to confirm that our results are not subject to selection bias or natural variation. Although male and female physiology could respond differently to hyperbaric hyperoxic conditions, we choose to include both sexes in this study to increase its clinical relevance (van Ooij et al, 2011; Lautridou et al, 2017). However, in a large study by Blanchet et al (2017) no significant effect of age, sex or BMI on exhaled breath profiles was found.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Also, as our results are in line with different study populations, collection methods and sample techniques, this tends to confirm that our results are not subject to selection bias or natural variation. Although male and female physiology could respond differently to hyperbaric hyperoxic conditions, we choose to include both sexes in this study to increase its clinical relevance (van Ooij et al, 2011; Lautridou et al, 2017). However, in a large study by Blanchet et al (2017) no significant effect of age, sex or BMI on exhaled breath profiles was found.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Also, dry diving affects cardiovascular function to a lesser degree than water immersion does ( Gaustad et al, 2010 ), and diving-naïve rats, as the ones in the present study, display different vascular responses than rats that have been exposed to diving regularly ( Berenji Ardestani et al, 2019 , 2020 ). Finally, epidemiological data from human divers as well as pre-clinical models show that DCS development is dictated by more factors than bubbles ( Cialoni et al, 2017 ; Lautridou et al, 2017 ). Additionally, as CO and SV were still falling at the time our experiment was terminated, we do not know how large the final decrease might be had the experiment been extended.…”
Section: Discussionmentioning
confidence: 99%
“…inheritability of Dcs protection is also considered in murines. 32 experimental studies with rats have shown that a single session of treadmill exercise, 20 hours before diving, reduced bubble levels and also mortality in a dramatic way. 33 in human divers also, pre-dive exercise has been shown influential 34 and, depending on the timing and intensity, seems to reduce or augment Vge counts.…”
Section: On the Bubble Sidementioning
confidence: 99%